Strategi Efektif dalam Pencegahan dan Penindakan Tindak Pidana Pembunuhan di Indonesia - Umam, Khairul; Abdillah, Rafli; Hakim, Alfin Rohman; Hernowo, Moh Sapto; Rosady, Ikbal Setiawan (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study discusses effective strategies for preventing and prosecuting murder crimes in Indonesia using a holistic approach. Social, economic, and environmental factors, such as poverty, unemployment, and domestic violence, are the primary triggers for the increasing crime rate. Prevention efforts include education, improving community security, and social interventions based on community involvement. Meanwhile, law enforcement requires a strong judicial system and the utilization of modern technology in investigations. The study results indicate that a combination of prevention strategies and firm law enforcement measures can significantly reduce murder rates. Collaboration between the government, law enforcement agencies, and the community is the key to creating a safer and more just environment.